Influence of Processing Induced Morphology on the Performance of PP Injected Intricate Pieces Modified with MWCNT as a Painting Aide - Costantino, María Alejandra (2021)
Carbon nanotubes are currently added to polymers to avoid extra-stages in the electrostatic painting process. However, the attained particle network after processing a final part could affect the mechanical properties and thermal stability of nanocomposites. It is then important to evaluate not only the functional properties, but also the overall performance of these pieces. In this work, boxes of polypropylene (PP) modified with multi-walled carbon nanotubes (MWCNT) were injection molded. Morphology induced by processing was characterized at different locations of the moldings to correlate the influence of in-homogeneities and flow pattern with the overall performance of the molded boxes. PP/MWCNT presented a better aesthetic quality and a markedly better thermal stability than pure PP. It was confirmed that the nanocomposite has high dielectric permittivity, low dielectric losses and relatively good DC conductivity. Regarding mechanical properties, MWCNT induced a slight improvement in flexural elastic modulus. Although fracture initiated at practically the same loading levels for both materials, the propagation energy was deteriorated by MWCNT presence. Differences in both electrical and mechanical behavior were found trough out the PP/MWCNT pieces as result of distinct MWCNT orientation and distribution. It was then concluded that processing has a great influence on parts performance.